Randomized controlled trial of a quadratus lumborum block with liposomal bupivacaine for postoperative analgesia in laparoscopic donor nephrectomy. Issue 9 (14th July 2021) - Gritsch, Hans Albin; Osbun, Nathan; Grogan, Tristan; Fero, Katherine E.; Partownavid, Parisa; Stockman, Joel; Sadoughi, Namjeh; Park, Edward; Miller, Eric; Blumberg, Jeremy; McDonald, Michelle; Cowan, Nicholas; et al.
Abstract: Perioperative pain management is an important consideration in early recovery and patient satisfaction following laparoscopic donor nephrectomy. Transmuscular quadratus lumborum block has been described to reduce pain and opioid usage following several abdominal surgeries. In this prospective single‐blind randomized controlled trial, we compared 52 patients who adhered to our institutional donor nephrectomy Early Recovery After Surgery pathway, which includes a laparoscopic‐guided transversus abdominus plane block, to 40 patients who additionally received a transmuscular quadratus lumborum block with liposomal bupivacaine. Compared to control patients, those who received the block spent longer in the operating room prior to the surgical start (65.4 vs. 51.6 min, P  < .001). Both groups had similar total hospital length of stay (33.3 h vs. 34.4 h, P  = .61). Pain scores from postoperative days 0–30, number of patients requiring opioids, postoperative nausea, and pain management satisfaction were similar between both groups. Patients who received the block consumed less opioid on postoperative day 1 compared to controls ( P  = .006). No complications were attributable to the block. The quadratus lumborum block provides a safe pain management adjunct for some patients, and may reduce opioid use in the early postoperative period when combined with our standard institutional protocol for kidney donors.